Intraventricular migration of silicone oil: A mimic of traumatic and neoplastic pathology. Issue 7 (July 2015) - Chiao, David; Ksendzovsky, Alexander; Buell, Thomas; Sheehan, Jason; Newman, Steven; Wintermark, Max
Abstract We describe an 80-year-old woman with intraventricular silicone oil mimicking traumatic pathology upon presentation to the emergency department after a ground-level fall. Intraventricular migration of silicone oil from prior intraocular endotamponade is rare having only been described in a handful of case reports. While it has a unique and characteristic appearance on imaging, intraventricular silicone oil can be confused with intraventricular hemorrhage or calcified ventricular neoplasms. Recognition and differentiation of intraventricular silicone oil from more sinister pathology is essential for the radiologist, neurologist and neurosurgeon and can be done with routine head CT scan. We discuss the imaging findings of intraventricular silicone oil and review the current understanding of this unusual phenomenon.